Transfer of squeezed coherent state using quantum teleportation of continuous variables - Aoi Fujimoto; Hiroyuki Ichihara (SICE Journal of Control, Measurement, and System Integration)
Quantum entanglement states in continuous-variable quantum teleportation can transfer any quantum state. However, errors occur in the quantum states before and after the transfer in scientific experiments because generating a perfect quantum entanglement is physically unattainable. This paper limits the quantum states transferred to squeezed coherent states and introduces a controller to classical information transfer in continuous-variable quantum teleportation to improve transfer accuracy. Under such a setup, we derived the optimal controller that maximizes the fidelity, independent of the measurement results and the value of the displacement of the squeezed coherent state.